DEVELOPING STUDENTS’ AESTHETIC PERCEPTION AND ARTISTIC THINKING IN THE PROCESS OF FINE ARTS EDUCATION - Bobomurodova Sojida Ablakulovna (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article explores the development of students’ aesthetic perception and artistic thinking within the framework of fine arts education in secondary schools. It emphasizes the psychological and pedagogical mechanisms that influence how students perceive beauty, form ideas, and express creativity through visual arts. The study highlights the importance of observation, imagination, and reflection as essential components of artistic thinking and proposes effective teaching strategies to enhance students’ aesthetic awareness and creative potential.